2021
DOI: 10.3847/1538-4357/ac2fa6
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Split-tail Heliosphere and the Role of Non-ideal Processes: A Comparison of the BU and Moscow Models

Abstract: Global models of the heliosphere are critical tools used in the interpretation of heliospheric observations. There are several three-dimensional magnetohydrodynamic (MHD) heliospheric models that rely on different strategies and assumptions. Until now only one paper has compared global heliosphere models, but without magnetic field effects. We compare the results of two different MHD models, the BU and Moscow models. Both models use identical boundary conditions to compare how different numerical approaches an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…As shown by Kornbleuth et al. ( 2021b ), the shape of both the split-tail and comet-tail models agree at the nose. Kornbleuth et al.…”
Section: The Split-tail Vs Comet-tail Debatesupporting
confidence: 55%
See 3 more Smart Citations
“…As shown by Kornbleuth et al. ( 2021b ), the shape of both the split-tail and comet-tail models agree at the nose. Kornbleuth et al.…”
Section: The Split-tail Vs Comet-tail Debatesupporting
confidence: 55%
“…Kornbleuth et al. ( 2021b ) compared the heliospheric solutions of the BU model and the Moscow model, which suppresses magnetic reconnection at the heliopause, and showed that regardless of heliopause treatment both models show a confinement of the solar wind plasma by the solar magnetic field (Fig. 14 ).…”
Section: The Bu Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…PUIs with parameter κ = 10 (1.57), density = , where n p is the plasma density and E p is the thermal energy of the plasma extracted from the BU MHD model of Kornbleuth et al (2021b). These fits are depicted with dashed lines in Figure 1 (green for SW, blue for transmitted PUIs, and red for the reflected and energized PUIs).…”
Section: Simulated Pui Distributionmentioning
confidence: 99%